Dairy products and risk of hepatocellular carcinoma: The European Prospective Investigation into Cancer and Nutrition. Issue 7 (7th March 2014) - Duarte‐Salles, Talita; Fedirko, Veronika; Stepien, Magdalena; Trichopoulou, Antonia; Bamia, Christina; Lagiou, Pagona; Lukanova, Annekatrin; Trepo, Elisabeth; Overvad, Kim; Tjønneland, Anne; Halkjær, Jytte; Boutron‐Ruault, Marie‐Christine; et al.
Abstract : Intake of dairy products has been associated with risk of some cancers, but findings are often inconsistent and information on hepatocellular carcinoma (HCC) risk is limited, particularly from prospective settings. The aim of our study was to investigate the association between consumption of total and specific dairy products (milk/cheese/yogurt) and their components (calcium/vitamin D/fats/protein), with first incident HCC ( N cases = 191) in the European Prospective Investigation into Cancer and Nutrition cohort, including a nested case–control subset ( N cases = 122) with the assessment of hepatitis B virus/hepatitis C virus infections status, liver damage and circulating insulin‐like growth factor (IGF)‐I levels. For cohort analyses, multivariable‐adjusted Cox proportional hazard models were used to estimate hazard ratios (HRs) and 95% confidence intervals (95% CI). For nested case–control analyses, conditional logistic regression was used to calculate odds ratios and 95% CI. A total of 477, 206 participants were followed‐up for an average of 11 years (person‐years follow‐up = 5, 415, 385). In the cohort study, a significant positive HCC risk association was observed for total dairy products (highest vs . lowest tertile, HR = 1.66, 95% CI: 1.13–2.43; p trend = 0.012), milk (HR = 1.51, 95% CI: 1.02–2.24; p trend = 0.049), and cheese (HR = 1.56, 95% CI: 1.02–2.38; p trend = 0.101), but not yogurt (HR = 0.94, 95% CI: 0.65–1.35). Dietary calcium, vitamin D, fat and protein from dairy sources were associated with increased HCC risk, whereas the same nutrients from nondairy sources showed inverse or null associations. In the nested case–control study, similar results were observed among hepatitis‐free individuals. Results from this large prospective cohort study suggest that higher consumption of dairy products, particularly milk and cheese, may be associated with increased HCC risk. Validation of these findings in other populations is necessary. Potential biologic mechanisms require further exploration. Abstract : What's New? Currently, the role of dairy product intake in the development of hepatocellular carcinoma (HCC) is unclear. Using detailed data from a large multi‐centric prospective cohort, this study investigated the association between consumption of total and specific dairy products with first incident HCC. The study found that higher dairy product consumption, particularly milk and cheese, was associated with increased HCC risk. Dietary calcium, vitamin D, fat and protein did not explain the observed associations. However, higher circulating IGF‐I levels may play a role.